The First Evidence of Round Oinophoros Workshop in Late Roman Tripolis - Duman, Bahadir (Rei Cretariae Romanae Fautorum Acta, 2022)
This study brings together the flasks uncovered at the ancient city of Tripolis in Lydia investigating their material and decoration; moulds uncovered were compared to the décor revealing the first evidence for local production at Tripolis in the 6th century AD. In the excavations conducted at Tripolis since 2012 a total of 271 fragments of oinophoroi and moulds used for their production, were uncovered at the Arched Structure, the House with Mosaics, Hierapolis Street East Portico, and Taberna 1. The clay fabric with muscovite content is of high quality and fine and almost all have silver-coloured mica coating which may be called silverwash. The wide colour range of the slip includes red, cream, brown and brick red. Moulded flasks feature decoration on both faces classified into geometric, floral and figural groups. In addition to geometric compositions with hourglass, wheel-of-fortune, boomerang and star motifs, architectural elements such as columns, colonnettes and aediculae are attested, as well as animal and human figures depicted in a variety of poses.